2015
DOI: 10.1158/1078-0432.ccr-14-1913
|View full text |Cite
|
Sign up to set email alerts
|

Development of Circulating Tumor Cell-Endocrine Therapy Index in Patients with Hormone Receptor–Positive Breast Cancer

Abstract: Background Endocrine therapy (ET) fails to induce a response in one-half of patients with hormone receptor (HR) positive metastatic breast cancer (MBC) and almost all will eventually become refractory to ET. Circulating Tumor Cells (CTC) are associated with worse prognosis in MBC patients, but enumeration alone is insufficient to predict the absolute odds of benefit from any therapy, including ET. We developed a multi-parameter CTC-Endocrine Therapy Index (CTC-ETI), which we hypothesize may predict resistance … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 42 publications
3
98
0
1
Order By: Relevance
“…To that end, a score based on CTC enumeration and characterization for estrogen receptor (ER), Bcl-2, HER2, and Ki67, the CTC-Endocrine Therapy Index (CTC-ETI; ref. 40), is currently being tested in the COMETI Phase II study (NCT01701050 ; Table 3). …”
Section: Ctc Characterizationmentioning
confidence: 99%
“…To that end, a score based on CTC enumeration and characterization for estrogen receptor (ER), Bcl-2, HER2, and Ki67, the CTC-Endocrine Therapy Index (CTC-ETI; ref. 40), is currently being tested in the COMETI Phase II study (NCT01701050 ; Table 3). …”
Section: Ctc Characterizationmentioning
confidence: 99%
“…Single-cell analysis of CTCs in ER þ metastatic breast cancer patients showed that in nearly half of evaluable patients, all CTCs were ER À , and the remaining patients harbored CTCs with mixed ER expression. Trials are currently under way to assess whether the endocrine therapy index of CTCs is correlated with patient outcome (28). Heterogeneous expression of the ERBB3 (HER3) and its ligand NRG1 have been reported in a variety of human cancers, including breast cancer, lung cancer, and glioblastoma (23,29,30).…”
Section: Heterogeneity In Ligand/receptor Expressionmentioning
confidence: 99%
“…Most of these studies show that a number of patients develop Her-2-positive CTCs, while the primary tumor was negative indicating a new possible treatment target for this group of patients. A recent article from Paoletti et al shows the use of the CXC kit for studying the development of resistance of breast cancer patients to the estrogen receptor downregulating drug fulvestrant [90,91]. This small study suggests a heterogeneous cause of resistance based on the expression of estrogen receptor (ER) and B-cell lymphoma 2 (BCL-2) on CTCs.…”
Section: Additional Reagents For Cell Labelingmentioning
confidence: 99%